Online on-board optimization of cutting parameter for energy efficient CNC milling - Tapoglou, Nikolaos; Mehnen, Jorn; Butans, Jevgenijs; Morar, Nicolau Iralal (Elsevier, 2016)
Energy efficiency is one of the main drivers for achieving sustainable manufacturing. Advances in machine tool design have reduced the energy consumption of such equipment, but still machine tools remain one of the most energy demanding equipment in a workshop. This study presents a novel approach aimed to improve the energy efficiency of machine tools through the online optimization of cutting conditions. The study is based on an industrial CNC controller with smart algorithms optimizing the cutting parameters to reduce the overall machining time while at the same time minimizing the peak energy consumption.
Keywords: Energy efficency; Optimization; Computer numerical control; CNC; Sustainable machining